The broken mirror - De la Cruz, Melissa, 1971- (De la Cruz, Melissa, 1971- Never after (Series), 2022)
Filomena and her Never After crew return when the evil Robin Hood leaguers the noble Lord Sharif of Nottingham. However, their new troubles are just beginning as the evil Queen Olga, at the request of her wicked daughter Cinderella, turns Prince Charming back into a frog after he wedded beautiful Hortense. Meanwhile, looming over all is the Prophecy. To stop the coming catastrophe, Filomena and her friends, old and new, must assemble the fearless warriors known as the League of Seven.